2014
DOI: 10.17759/psyedu.2014060404
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of the Emotional Content of Music Depending on the Characteristics of the Musical Material and Experience of Students

Abstract: We studied the effect of the factors affecting the recognition of the emotional content of the music. We tested hypotheses about the influence of the valence of the music, ethnic style and the listening experience on the success of music recognition. The empirical study involved 26 Russian musicians (average age of 25,7 years). For the study of musical perception we used bipolar semantic differential. We revealed that the valence of music material affects the recognition of the emotional content of music, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…It was shown in the previous research that the selected scales made it possible to divide different groups of subjects. For instance, musicians could be distinguished from non-musicians, as well as significant differences in the perception of recipients could be identified when evaluating different types of music (Knyazeva, 2010(Knyazeva, , 2014Knyazeva & Toropova, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in the previous research that the selected scales made it possible to divide different groups of subjects. For instance, musicians could be distinguished from non-musicians, as well as significant differences in the perception of recipients could be identified when evaluating different types of music (Knyazeva, 2010(Knyazeva, , 2014Knyazeva & Toropova, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Investigations into the behavior of people of different cultures have found that in the sphere of the expression of emotions, there are both universal types of reactions and those specific to certain cultures. That is, the language of emotions contains both common and cultural-specific elements (Esposito et al, 2009;Knyazeva, 2014;Knyazeva & Toropova, 2014). The elements that have differences among the representatives of various cultures are rather a result of socialization and therefore, are subject not only to a natural training but a purposeful one, as well.…”
Section: заключениеmentioning
confidence: 99%